2000
DOI: 10.1021/es990849j
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Phenol and Benzoate as Intermediates of Anaerobic Benzene Biodegradation under Different Terminal Electron-Accepting Conditions

Abstract: A sulfate-reducing bacterial enrichment that anaerobically metabolized benzene was obtained from a petroleumcontaminated aquifer. During biodegradation, we observed the transient accumulation of phenol and benzoate as putative benzene intermediates. As these compounds are intermediates in many anaerobic metabolic pathways, we investigated their relation to anaerobic benzene decay with 13 C-labeled starting material. We were able to confirm the presence of [ 13 C]phenol and [ 13 C]benzoate as intermediates of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 44 publications
6
84
1
2
Order By: Relevance
“…The environmental implications of such extracellular processing of benzene to more readily degradable substrates and the availability of these substrates to other organisms in the natural environment are currently unknown. Although the concentrations of phenol and benzoate detected in our studies are very low, they are in agreement with previous reports on intermediates formed during anaerobic benzene and toluene degradation (4,10). Prior studies detected phenol, cyclohexanone, and propionate as potential intermediates in undefined methanogenic enrichments incubated with benzene (21,37).…”
Section: Mechanism Of Hydroxylationsupporting
confidence: 92%
See 2 more Smart Citations
“…The environmental implications of such extracellular processing of benzene to more readily degradable substrates and the availability of these substrates to other organisms in the natural environment are currently unknown. Although the concentrations of phenol and benzoate detected in our studies are very low, they are in agreement with previous reports on intermediates formed during anaerobic benzene and toluene degradation (4,10). Prior studies detected phenol, cyclohexanone, and propionate as potential intermediates in undefined methanogenic enrichments incubated with benzene (21,37).…”
Section: Mechanism Of Hydroxylationsupporting
confidence: 92%
“…Prior studies detected phenol, cyclohexanone, and propionate as potential intermediates in undefined methanogenic enrichments incubated with benzene (21,37). Similarly, phenol, benzoate, and acetate were also detected in benzene-degrading iron-reducing and sulfate-reducing sediments (10). As Dechloromonas species are not known to grow by Fe(III) reduction, by sulfate reduction, or through syntrophic interactions with methanogenic bacteria (13,17), it is unlikely that organisms closely related to strain RCB or JJ are involved in the benzene metabolism observed in the previous studies.…”
Section: Mechanism Of Hydroxylationmentioning
confidence: 71%
See 1 more Smart Citation
“…Phenol and benzoate, which have been detected in the culture medium of methanogenic, sulfate-reducing, and iron-reducing mixed cultures, are thought to be potential metabolites of anaerobic benzene biodegradation. A direct methylation of benzene to toluene has also been proposed (49,65,365). Interestingly, the anaerobic nitrate-dependent benzene degradation by Dechloromonas aromatica strain RCB appears to involve an initial hydroxylation with the formation of phenol.…”
Section: Vol 73 2009 Anaerobic Biodegradation Of Aromatics 101mentioning
confidence: 99%
“…However, most studies with consortia have shown that benzene seems to be recalcitrant to biodegradation under denitrifying conditions in both cases: in mixtures and as a sole electron donor. In this sense, it has been suggested that benzene is not consumed due to the lack of oxidizing enzymes (Gülensoy & Alvarez, 1999) and/or to the high structural stability of benzene (Cadwell & Sufita, 2000). Likewise, toxic effects on bacteria cell membranes have been proposed (Sikkema et al, 1994).…”
Section: Nitrate and Btx Removalmentioning
confidence: 99%